Visual Interpretations, Cartoons, and Caricatures of Student and Youth Cultures in University Yearbooks, 1898–1930 - Panayotidis, E.; Stortz, Paul (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractStudents have always been integral in the development of the university in Canada. Driven by personal, professional, and political agendas, student experiences, understandings, and narratives helped construct the academic and intellectual cultures of universities. In their relationships with professors, administrators, and the spaces they inhabit, students crucially contributed to the university as a historically vibrant idea and social institution. As cast by the students, the university was clearly expressed in variant and creative ways through the annual yearbook. In particular, within the yearbook, the practice of parody in cartoons and caricatures was powerful in depicting the imagined worlds of academe as seen through the students’ eyes, and importantly how the students saw themselves and their life on campus. Using yearbooks from three universities — Toronto, Alberta, and British Columbia – visual images are studied that reveal underlying intentions to comment, marginalize, ridicule, and esteem groups of students according to both ascribed and self-imposed socialized hierarchical structures and codes of expectations and behaviour. Among the universities, the visual satire was consistent in tone and image, exposing the historic place and activities of students in the early university and in society, the contingent formation of student identities, and the nature of the pursuit of academic knowledge and credentials by youth in early-twentieth Century Canada.